Detection of phenolic compounds in Terfezia claveryi truffle’s extract by LC-MS/MS, Formulation and in-vitro evaluation (مجلة جامعة دمشق للعلوم الطبية, 2021)
Recently, the interest in natural materials has increased for safe and effective products free of chemical compounds. In this paper, phenolic compounds of ethanolic 70% extract of black truffle T.claveryi, a widespread mushroom in Syria, was studied by using LC-MS/MS technique. Furthermore the dried extracts were formulated in five semi-solid formulas, their physicochemical properties and the release profiles of extract’s compounds from these formulas were in-vitro evaluated. It has been predicted about 15 phenolic compounds in the extract; as p-Hydroxy benzoic acid, gallic and syringic acids, these compounds have therapeutic and cosmetic benefits to skin. Emulsifying and gelling agents were contributed to improve of formulas characteristics for their future application on the skin. The gelling agents and hydrophobic content of the formulas have conducted to delayed release of extract’s compounds.